Outdoor Behavioral Health Care: A Longitudinal Assessment of Young Adult Outcomes. (January 2017) - Roberts, Sean D.; Stroud, Daniel; Hoag, Matthew J.; Massey, Katie E.
Abstract : This article details a 3‐year outdoor behavioral health care outcome study. Hierarchical linear modeling was used to analyze data from 186 young adults in a wilderness therapy program. Participants completed the Outcome Questionnaire–45.2 (Lambert et al., 2004 ) 6 times from Week 1 to 18‐month postdischarge follow‐up. Results indicated that clinically and statistically significant change occurred in treatment. Rates of change varied, and posttreatment scores remained stable, thus demonstrating that in‐treatment gains were maintained. Implications and recommendations for future research are discussed.